28 Diagnostic coding through an innovative molecular electronic outcome form (mecof): a quality improvement project in the clinical genetics department. (4th October 2017) - Faravelli, F; Kumar, A; Williams, E; Jones, K; Jones, W; Clement, E; Menzies, L; Gough, Paul; Barnicoat, A
Abstract : Background: With costs of genome-wide sequencing dramatically falling over recent years many more individuals with rare diseases are receiving a molecular diagnosis for their disorder. With molecular diagnosis comes the possibility of management and treatment trials based on the individual's specific condition. Hospital coding systems are vital for clinical audit and for recontacting patients when new information becomes available. As we move towards personalised medicine, incorporating the molecular diagnosis into any such system is crucial to allow identification of patients with specific genetic conditions. An analysis of the available resource for diagnostic coding in the clinical genetics department revealed limitations, mostly related to the existing diagnosis list. Additionally, some staff reported our previous coding system was too cumbersome to use, resulting in poor compliance. We aimed to improve the coding and follow-up plan recording process to incorporate molecular data and increase staff compliance. Methods: In the context of an innovative clinical outcome system, we devised a user–friendly comprehensive method to facilitate diagnostic coding and follow up recording for each patient. Results: The new coding system includes a clinical diagnosis, a molecular diagnosis and a status. The clinical and molecular diagnoses are sourced by publicly available lists generated by Human Phenotype Ontology (HPO) and are expected to be dynamic, evolving as genetic knowledge advances. In genetic, we often see family members who might not be affected by the condition and the status field reflects this peculiarity. The system is quick and effective, as demonstrated by the high compliance among clinicians using it. A recent preliminary study has allowed an audit of the current practice (presented elsewhere) Conclusion: We have demonstrated the use of our 'molecular electronic coding and follow up' system (MECoF), which could be adapted for use trust wide. Recording of molecular data and the ability to recall patients with specific molecular disorders will be vital in delivering high quality care for patients with Genetic disorders in the future.